Analisis Feminisme Liberal pada Antologi Cerpen Perempuan dan Perempuan Karya Bagus Satria - Jumaroh Ristian Ningsih; Retno Wulandari; Cintya Nurika Irma (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The purpose of this study is to describe, analyze, and examine the feminism contained in the anthology of the short story